Modelagem de nicho ecológico de Bactrocera carambolae Drew & Hancock (Diptera: Tephritidae): risco de dispersão e previsões futuras - Braga, Luiza Nascimento (2022)
The use of species ecological niche modeling is a well-accepted approach to predicting the possible extent of suitable habitat for species and can contribute to effective management and preventive measures. CLIMEX is one of the most used modeling software, capable of predicting the climatic suitability of a region for the target species, based on the premise that, knowing the place where a species lives, one can infer about the climatic conditions tolerated by it; and thus simulate the mechanisms that limit their geographic distribution. The software has been used mainly to model species with the greatest damage potential in large countries, continents or the world. The objective of this study was to determine the predictive geographic distribution of Bactrocera carambolae Drew & Hancock (Diptera: Tephritidae) in the world, an extremely polyphagous and harmful fruit pest. Native to Southeast Asia and introduced to South America, the entry or dispersal of the carambola fruit fly in fruit-producing areas can result in costly control costs and loss of import markets. To assist in pre- and post-border biosecurity strategies for this pest, CLIMEX ecological niche modeling estimated the potential dispersal of B. carambolae around the world, in the current (2022) and future (2100) climate scenario, taking into account the effects of climate change. Under current climatic conditions, the model indicates that B. carambolae can establish itself in all tropical and subtropical regions of the globe, with emphasis on the following continents: Africa, South America, Central America, Asia and Oceania; not being a relevant threat to Europe, North America and Antarctica. In a simulation of a future scenario, where the terrestrial temperature will increase by 3 °C, the ecological niche of the species will suffer a reduction, although it will still remain concentrated in the intertropical zone. The level of environmental adequacy will be reduced in many countries and many others will no longer be threatened by the dispersal of the pest insect. This is due to increased heat stress and reduced humidity.